2022
DOI: 10.1161/strokeaha.122.038685
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Occurrence After a Cerebral Venous Thrombosis: A Nationwide Registry Study

Abstract: Sources of FundingThis study was supported by the Government's Special Financial Transfer tied to academic research in Health Sciences (Finland).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…27 The reason behind the high risk of intracranial herniation in patients with malignant CVST is the high clot load generated as a result of the prothrombotic state triggered by many mechanisms, such as late initiation of anticoagulant therapy in patients and damage to the blood-brain barrier. 29,30 Our results are consistent with those reported in the literature, 7 wherein poor clinical outcomes and death were more frequent in CVST patients with intracranial herniation.…”
Section: Discussionsupporting
confidence: 92%
“…27 The reason behind the high risk of intracranial herniation in patients with malignant CVST is the high clot load generated as a result of the prothrombotic state triggered by many mechanisms, such as late initiation of anticoagulant therapy in patients and damage to the blood-brain barrier. 29,30 Our results are consistent with those reported in the literature, 7 wherein poor clinical outcomes and death were more frequent in CVST patients with intracranial herniation.…”
Section: Discussionsupporting
confidence: 92%
“…Although cancer is a well-established cause of other venous thromboses, such as DVT/PE, 5 few investigations have focused on CVT. 16,17 Using Finnish registries, Sipilä et al 17 reported that among 589 patients with CVT diagnosed between 2005 and 2007, 2.3% received a cancer diagnosis within 2 years following CVT diagnosis. The absolute risk found in our study (eg, 1.9% after 12 months) resembles that finding.…”
Section: Discussionmentioning
confidence: 99%
“…28 Although cancer is a well-established cause of other venous thromboses, such as DVT/PE, 5 few investigations have focused on CVT. 16,17 Using Finnish registries, Sipilä et al 17 adjusted odds ratio of cancer of 4.9 (95% CI, 3.5-6.8), suggesting that cancer is a potent risk factor for CVT. We also assessed the impact of a CVT diagnosis on cancer prognosis, extending previous research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations